Endogenous endophthalmitis as a complication of Klebsiella pneumoniae liver abscess - Korycińska, Karolina; Cisek, Agnieszka; Spyra, Mariusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2024)
Endogenous endophthalmitis is a rare but significant complication of systemic infections. It is associated with serious and unfavorable consequences both for the functions of the organ of vision and the general condition of the patient. Early diagnosis and prompt implementation of treatment are crucial in the management process. The article presents two clinical cases of patients with endogenous endophthalmitis caused by Klebsiella pneumoniae liver abscesses.